Case Study of BELL E-learning: Award-Winning, Interactive E-learning on a Nonprofit Budget - Marquart, Matthea; Jones Rizzi, Zora (International Journal of Advanced Corporate Learning (iJAC), 2009)
BELL (Building Educated Leaders for Life) is a nonprofit organization offering academic tutoring to elementary school children from low-income, urban communities. BELL launched a blended learning training for the tutoring staff working in its summer program in 2008, and won Training Magazineâ??s Blended Learning and Performance Project of the Year. The e-learning from that blended learning training is discussed in this paper.